Post-production Losses in Iodine Concentration of Salt Hamper the Control of Iodine Deficiency Disorders: A Case Study in Northern Ethiopia (Journal of Health, Population and Nutrition, 2010)
Iodine is essential for good function of the thyroid, and its deficiency is of public-health importance inEthiopia. Iodization of salt is an effective and sustainable strategy to prevent and control iodine deficiencyin large populations. The effectiveness of salt-iodization programmes depends on the conservation of iodineconcentration in salt at various stages of the supply-chain. The overall objective of the study was toassess the loss of iodine in salt from production to consumption and to estimate the proportion of adults,especially pregnant women, at risk of dietary iodine insufficiency. A cross-sectional study was conductedduring February-April 2007 in northern Ethiopia. Iodine concentrations of salt samples from producers(n=41), retailers (n=7), and consumers (n=32) were determined using iodiometric titration. A risk assessmentwas conducted for dietary iodine insufficiency among adults, including pregnant women, usinga semi-probabilistic approach. The concentration of iodine in the sampled salts decreased by 57% fromthe production site to the consumers. The assessment of exposure showed that adults in 63% (n=20) ofthe households, including 90% (n=29) with pregnant women, were at risk of insufficient iodine intake. Amonitoring and evaluation system needs to be established to ensure adequate supply of iodine along thedistribution chain. Special attention is needed for the retailers and consumers. At these levels, disseminationof information regarding proper storage and handling of iodized salt is necessary to address the reportedloss of iodine from salt.Key words: Cross-sectional studies; Iodine; Iodine deficiency; Salt; EthiopiaDOI: 10.3329/jhpn.v28i3.5550J HEALTH POPUL NUTR 2010 Jun;28(3):238-244